FAKTOR PENYEBAB TERJADINYA PERSELISIHAN DAN PERTENGKARAN TERUS MENERUS DI PENGADILAN AGAMA TILAMUTA - MASIONU, ABDUL RAHMAN; WANTU, FENCE M; KAMBA, SRI NANANG MEISKE (Universitas Mahasaraswati K. Mataram, 2024)
This research is motivated by the difficulty of maintaining and creating a harmonious household. Differences of opinion, lack of communication and various kinds of problems that trigger disputes and disputes between the two. The aims of this research are (1) to determine the factors that cause continuous disputes and quarrels and (2) to determine the consequences of continuous disputes and quarrels. This research was carried out at the Tilamuta Religious Court using a qualitative approach with an empirical research type. The results of the research show that the causes of disputes and quarrels are; a) Economic problems, household needs are not met while there are children and wife's needs that must be met. b) Third party interference, can come from families who are excessively involved in household relationships or from other people. c) Polygamy is unhealthy, the husband is unable to act fairly and is unable to take responsibility for his two wives. d) Domestic violence/abuse occurs, lack of control of each other's egos and coupled with the husband not being able to control his emotions so he takes it out on his wife. The consequences arising from continuous disputes and quarrels include: (a) Disruption in fulfilling the rights and obligations of husband and wife, (b) Problems regarding child custody, (c) Division of joint Assets